PORE SIZE AND GEOMETRY OF RESERVOIR ROCKS USED AS KEY FACTOR FOR DRILLING AND COMPLETION FLUID DESIGN OF OIL WELLS - Enbaia, Ali Elsaeh; Ramdzani, Illiya Amalina Binti Ahmad (European Scientific Journal, ESJ, 2014)
The initial poor well productivity in many cases is a result of the lack of control for fluid loss and the invasion during drilling and completion operations. Rock formation attributes like pore geometry within the rock should be considered as a key factor in the design and selection of reservoir drilling and completion fluids with capabilities to control the fluid loss and the invasion effectively. Drilling and completion engineers as well as related professionals need to have a better understanding of sizes and shapes within the reservoir pore system in order to formulate optimum fluids to minimize the formation damage. The size and shape of pores, pore geometry, is usually determined using direct visual methods like petro graphic thin section analysis and scanning electron microscopy (SEM). The Mercury injection porosimetry has also been used as an indirect method to get the pores’ size. Limitations of pore geometry SEM measurements have been revised and applied in both synthetic and real formation samples with the usage of fundamental concepts, methods and available data of pores. The digital image processing and analysis are presented as an applied technology tool used to enhance the pore system interpretation, as soon as images were obtained through conventional SEM practice. Concepts like pore throat, body, connectivity and 2D to 3D analysis were discussed in detail to make the actual pore geometry information more accessible and useful to drilling and completion fluid design teams.